Revitalisasi Guru Al-Islam dan Kemuhammadiyahan (AIK) dengan Pengembangan Media Pembelajaran Model Design Thinking Berbasis Macromedia Flash - Muzakki, Muhammad; Raharja, Endra Putra; Kasri, Muhammad Ali; Alim, Hijrah Nur; Ambali, Wahyu; Sutikno, Aldilla Yulia Wiellys (STAI Auliaurrasyidin Tembilahan, 2024)
This initiative aims to address the challenges in teaching Al-Islam and Kemuhammadiyahan (AIK) at Muhammadiyah schools in Sorong, where teachers lack an understanding of Muhammadiyah ideology and cadre patterns, as well as the ability to create engaging learning media. The initiative was conducted in collaboration with the DIKDASMEN and PNF Assemblies of Muhammadiyah Sorong, focusing on revitalizing AIK teachers through learning media based on design thinking and Macromedia Flash. The activities included workshops using andragogical methods and the establishment of AIK teacher communities to address implementation issues post-activity. The results demonstrated improved management of educational human resources, enhanced understanding of Muhammadiyah ideology and cadre patterns among AIK teachers, and improved skills in creating engaging and modern learning media.